The English and the Normans ethnic hostility, assimilation, and identity, 1066-c.1220 - Thomas, Hugh M. (Oxford University Press, 2003)
This work challenges the complacency about the inevitability of assimilation and of the Anglicization of Normans after 1066. Drawing on a variety of sources, it provides a case study in pre-modern ethnic relations, shedding light on some important developments in English history.